Pengukuran Kinerja Keuangan Bus Menggunakan Islamicity Performance Index - Mabruroh, Mabruroh; Supriyanto, Trisiladi; Ayyuniyah, Qurroh (Jurnal Ilmiah Ekonomi Islam, 2024)
The development of Islamic banking in Indonesia today has experienced a rapid increase both in quantity and quality. As an institution that operates based on sharia principles, Islamic banks have different characteristics and assessments of financial performance from conventional banks. Islamicity Performance Index is one of the new concepts as a method that can be used to evaluate the performance of Islamic banks which are not only financially but also able to evaluate the principles of fairness and halalness of an Islamic banking.This study aims to reveal the application of sharia principles to the performance of Islamic Commercial Banks in Indonesia for the 2017-2020 period by using the Islamicity Performance Index. The ratios used are Profit Sharing Ratio, Zakat Performance Ratio, Equitable Distribution Ratio, Directors-Employees Welfare Ratio, Islamic Investment Vs Non-Islamic Investment, Islamic Income Vs Non-Islamic Income and the AAOIFI Index. The data used in this research is secondary data. The population of this study is all Islamic Commercial Banks in Indonesia for the 2017-2020 period, with a sample of five banks. Sampling was carried out using purposive sampling method. From the results of this study, it was found that the performance of Islamic banks can be said to be "unsatisfactory" because they have implemented profit sharing in accordance with Islamic rules and sharia, although the share of profit sharing is still lower than other financing. Islamic banks in issuing zakat are still not maximal, namely below 1%. In distribution to stakeholders, Islamic banks have issued qards and donations, providing employee salaries and net income which are still not felt by the benefits of the stakeholders. In the comparison of the average salary of directors with the average salary of employees, there is a difference in the average salary which is too high so that justice must be upheld in Islamic institutions to reduce the gap between directors and employees. Islamic Commercial Banks invest their funds in the halal sector with a ratio yield of 100% and already have 99% income from halal income. Shariah principles set by AAOIFI as a whole have been fulfilled by Sharia Commercial Banks in terms of promotion costs, risk-weighted assets, non-performing financing, interest-free income, profitability and distribution of zakat, although many of these points have not been maximized. The conclusion is that Islamic Commercial Banks in Indonesia still need to evaluate their performance for a better future.